2012
DOI: 10.12688/f1000research.1-40.v2
|View full text |Cite
|
Sign up to set email alerts
|

Local indigenous knowledge about some medicinal plants in and around Kakamega forest in western Kenya

Abstract: Kakamega forest is Kenya's only rainforest and is distinguishably rich in biodiversity but threatened by agricultural encroachment and other forms of human activity. It is also one of Kenya's Important Bird Areas and a significant source of natural products to neighboring rural communities, such as medicinal plants, food, wood and other fibers. By using structured questionnaires for direct interviews, local indigenous knowledge was tapped through involvement of a focal group of elderly key informants in three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 18 publications
3
16
0
Order By: Relevance
“…For example, a survey in Uganda by Tugume et al (2016) on the communities around Mabira Central Forest showed that 190 species are used as medicines, such as drugs for malaria, hypertension, anemia, and to suppress vomiting. A study in Kakamega forest, Western Kenya, showed 40 plant species that could potentially be used for medicinal purposes for local communities (Otieno and Analo 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a survey in Uganda by Tugume et al (2016) on the communities around Mabira Central Forest showed that 190 species are used as medicines, such as drugs for malaria, hypertension, anemia, and to suppress vomiting. A study in Kakamega forest, Western Kenya, showed 40 plant species that could potentially be used for medicinal purposes for local communities (Otieno and Analo 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Recording and preserving the traditional knowledge on medicinal plants has become very important practice in recent times [17]. Several ethnobotanical and ethnopharmacological research studies have been published documenting Kenya's medicinal plant knowledge and use: Marakwet county [11,18], Northern Kenya [19], Siaya county [20,21], Tugen [22], Machakos county [23,24], Samburu county [25][26][27], Sekanani Valley, Maasai Mara [28], Kajiado county [29][30][31][32][33], Embu and Mbeere county [34], Makueni county [35], Mount Elgon [36], Nakuru county [37], Nandi county [38][39][40][41], Tharaka Nithi county [42], Kakamega county [43][44][45][46][47], Kitui county [48], Elgeyo Marakwet county [49], Kericho county [50], Machakos county [51], Narok county [52][53][54], Trans-Mara county [55], Kilifi county [56]. However, in Kenya, many areas and ethnic societies are yet to be ethno botanically surveyed.…”
Section: Introductionmentioning
confidence: 99%
“…An estimated 1,200 plant species in Kenya are reported to have a medicinal value [26]. In Kenya, ethnobotanical studies involving various ethnic groups have been done [16,17,21,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. e local communities who use natural resources have interacted with the biodiversity over the years and hence have accumulated important traditional knowledge regarding their use [40].…”
Section: Introductionmentioning
confidence: 99%